Influence of Ca substitution on microstructure and electrical properties of Ba(Zr,Ti)O3 ceramics - Pisitpipathsin N. (2014)
In the present work, lead-free (Ba1-xCax)(Zr 0.04Ti0.96)O3 (x=0.00-0.09) ceramics were fabricated via a solid-state reaction method. The microstructure and electrical properties of the ceramics were investigated. The microstructure of the BCZT ceramics showed a core shell structure at compositions of x=0.03 and 0.06. The substitution of small amount of Ba2+ by Ca2+ resulted in an improvement of the piezoelectric, dielectric and ferroelectric properties of the ceramics. The orthorhombic-tetragonal phase transition was found in the composition of x≤0.03. Piezoelectric coefficient of d33∼392 pC/N and lowest Ec∼3.3 kV/cm with highest Pr∼14.1 μC/cm2 were obtained for the composition of x=0.03 while its Curie temperature (TC) was as high as 125 °C. However, the ferroelectric to paraelectric transition temperature had slightly shifted towards room temperature with increasing Ca2+ concentration. © 2012 Elsevier Ltd and Techna Group S.r.l.